Attenuation of UVB-Induced Photo-Aging by Polyphenolic-Rich Spatholobus Suberectus Stem Extract Via Modulation of MAPK/AP-1/MMPs Signaling in Human Keratinocytes - Kyoo-Ri Kwon (Nutrients, 2019)
It is well known that ultraviolet light activates mitogen-activated protein (MAP) kinase by increasing the reactive oxygen species (ROS) in the body, enhancing activating protein 1(AP-1) complexes (c-Jun and c-Fos), increasing matrix metalloproteinases (MMPs) and degrading collagen and elastin. In this study, we confirmed that polyphenolic rich Spatholobus suberectus (SS) stem extracts suppressed ultraviolet (UV)-induced photo-aging. The major active components of SS stem extracts were identified as gallic acid, catechin, vanillic acid, syringic acid and epicatechin. The aqueous and ethanolic extracts of the stem of SS (SSW and SSE, respectively) significantly reduced the elastase enzyme activity. Moreover, both extracts were suppressed the ROS generation and cellular damage induced by UVB in HaCaT cells. Our results also revealed that SSE could regulate the expression of MMPs, tissue inhibitor of matrix metalloproteinase (TIMP)-1, collagen type I alpha 1 (COL1A1), elastin (ELN) and hyaluronan synthase 2 (HAS2) at their transcriptional and translational level. Furthermore, SSE was blocked the UVB-induced phosphorylation of mitogen-activated protein kinases (MAPKs), nuclear factor-kappa B (NF-κB) and c-Jun. Moreover, combination of syringic acid, epicatechin and vanillic acid showed strong synergistic effects on elastase inhibition activity, in which the combination index (CI) was 0.28. Overall, these results strongly suggest that the polyphenolics of SSE exert anti-ageing potential as a natural biomaterial to inhibit UVB-induced photo-aging.